Mesiodens and a supernumerary tooth as a cause of disorders in the eruption of teeth 21 and 22 – a case report - Pinkowska-Prasal, Małgorzata; Bialkowska-Glowacka, Jolanta; Ratajek-Gruda, Monika; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
The article presents a case of surgical treatment of an 11 y.o. boy, who was diagnosed with a mesiodens and a supernumerary impacted tooth at the same time.